A micro-photoluminescence study of vertically stacked InGaAs-GaAs double-layer quantum dots - Choi, YC; Kim, TG; Park, YM; Park, YJ (KOREAN PHYSICAL SOC, 2004)
The optical properties of In0.5Ga0.5As-GaAs single-layer quantum dots (SL-QDs) and three vertically stacked double-layer quantum dots (DL-QDs) with different spacer thicknesses, grown by solid-source molecular beam epitaxy (MBE) in Stranski-Krastonow (S-K) growth mode, are investigated by micro-photoluminescence (mu-PL) spectroscopy. Interestingly, mu-PL spectra of all DL-QDs are observed at energies lower by approximately 40 meV, compared with those of SL-QDs, indicating the effective coupling of DL-QDs, along with multiple sub-peaks on the right shoulder of the luminescence center. A reduction in overall energies of the quantum dot (QD) in terms of electronic coupling, and the creation of multiple energy states in terms of mutual interactions among the DL-QDs of different sizes and shapes, are considered to be possible reasons for this phenomenon. The excitation-power-dependent mu-PL spectra also show state-filling effects in the lowest energy levels of the DL-QDs.
Keywords: OPTICAL-PROPERTIES; COMPUTATION; RESONANCE; SURFACES; ISLANDS; STATES; GROWTH